Tempo i kierunki zmian składu gatunkowego drzewostanów naturalnych w wybranych zbiorowiskach leśnych Puszczy Białowieskiej - Paluch, Rafał (Leśne Prace Badawcze, 2014)
The main aim of the study was to determine changes in the species composition and structure of natural tree stands in the Białowieża Forest (BF), which occurred in the years 1975-2012, as well as to evaluate their trends, directions and rate. The study was carried out on 121 permanent research plots (50×50m), which represented the most important forest phytocenoses in BF, i.e. fresh pine-whortleberry forest Vaccinio vitis-idaeae-Pinetum Sokoł. 1980, fresh mixed spruce-reed grass forest Calamagrostio-Piceetum Sokoł. 1968, oligotrophic form of hornbeam – bastard balm forest Melitti-Carpinetum Sokoł. 1976, different forms of linden- hornbeam forest: Tilio-Carpinetum Tracz. 1962, alder-ash forest Fraxino-Alnetum W. Mat. 1952 and sub-boreal spruce forest on bog moss Sphagno girgenshonii-Piceetum Polak. 1962. On the plots selected, there was measured the diameter at breast height (DBH) of all trees, as well as every tree and shrub up to 1.3 m high was counted and described with reference to species. The measurements and observations were regularly repeated every 10-15 years. The results showed that over the last period of nearly 40 years, there has increased a share of common hornbeam Carpinus betulus L. in the structure of forest stands in numerous BF associations. This tree species has expanded into different forest habitats including poor, medium fertile and wetland sites. The results obtained indicate a trend towards formation of linden-hornbeam forests in BF phytocenoses. The most evident changes were recorded in hornbeam – bastard balm forest. In natural conditions of the majority of forest associations analyzed, there prevailed hornbeam trees in forest regeneration, except for the stands in fresh mixed pine forest and spruce forest on bog moss. In the latter two cases, hornbeam showed signs of its presence in the last observation period. Norway spruce ( Picea abies L.) retreated into oligotrophic forest associations. In the recent decades, spruce populations have been dramatically reduced in the stands in mixed coniferous and different kinds of broadleaved forests. There have also decreased a share of light-demanding tree species, such as Scots pine ( Pinus silvestris L.), pedunculate oak ( Quercus robur L.) and silver birch ( Betula pendula L.) in BF tree stands, including their regeneration-layer. Especially, Scots pine regeneration has not been successful. In the short period of time (about 15 years) there has been observed rapid and outsized reduction of ash Fraxinus excelsior L. populations in natural conditions of alder-ash forests. All through the last 10-15 years, there has been also observed increased rate of change in stand species composition. The trend and rate of change in stand species composition point out to a possibility of human intervention towards stimulation of natural regeneration so as to preserve valuable populations of threatened tree species in the Białowieża Forest.